INFORMATION ON THE USE OF PREDNISOLONE (American Journal of Interdisciplinary Research and Development, 2025)
Prednisolone is a corticosteroid medication used to treat a wide range of inflammatory and autoimmune conditions. It mimics the effects of cortisol, a hormone naturally produced by the adrenal glands, and works by suppressing inflammation and modulating the immune response. Hyperemia, swelling, itching, urticaria, rash, steroid reactions, purpura, telangiectasias, itching, irritation and drying of the skin may occur in the areas where the drug is applied, especially when the drug is used in patients who cannot personally absorb the components of the drug.